ChemInform Abstract: The New Barium Compound Ba4Al7+x: Formation and Crystal Structure. Issue 33 (July 2016) - Prots, Yurii; Lange, Felix; Drathen, Christina; Schmidt, Marcus; Grin, Yuri
Abstract: A combination of powder XRD with in‐situ high‐temperature synchrotron XRD and DSC is used to show that Ba21 Al40, Ba3 Al5, Ba7 Al10, and Ba4 Al5 decompose peritectically at 914, 826, 756, and 732°C, respectively.